Role of Fine Needle Aspiration Cytology in the Diagnosis of Parotid Gland Tumors: Analysis of 193 Cases - Dhanani,Rahim (2020)
Abstract Introduction Parotid gland tumors include a wide variety of inflammatory and neoplastic diseases. The majority of these tumors are benign (80%), which usually require superficial parotidectomy, while the incidence of malignant tumors is lower (20%), requiring more radical surgery with or without neck dissection. The diagnosis cannot be established on the basis of clinical history and simple physical examination and requires complementary diagnostic methods. Fine needle aspiration cytology (FNAC) guided by ultrasound is a widely used diagnostic tool to evaluate parotid swellings. Objective To determine the sensitivity, specificity, positive and negative predictive values and diagnostic accuracy of FNAC in the diagnosis of parotid gland tumors. Methods A retrospective chart review of 193 patients who underwent preoperative FNAC and parotidectomy at the Aga Khan University Hospital, Karachi, Pakistan, from the period of January 2000 to December 2015 was performed. Results Out of 193 patients undergoing parotidectomy, 110 (57%) were males and 83 (43%) were females, the mean age being 48.21 and 43.76 years old, respectively. The mean duration of the symptoms was 41.33 months, and the most common symptom was preauricular swelling present in all patients, followed by pain, which was present in 29 patients (15%) and facial nerve weakness in 6 patients (3.1%). Fine needle aspiration cytology was performed preoperatively and the results were compared with the final histopathology, which showed sensitivity of 88.9%, specificity of 97.9%, positive predictive value of 93%, negative predictive value of 96.7% and diagnostic accuracy of 95.8%. Conclusion Our results suggest that FNAC is relatively an accurate method for preoperative diagnosis of parotid swelling and can prove to be a valuable tool for preoperative counseling of the nature of the disease and prognosis.